Antenas fractales - Suárez Fajardo, Carlos Arturo; Gaona García, Elvis Eduardo; Rincón Reyes, Diego Yecid (Ingeniería, 2000)
Abstract: The multiband behavior of the fractal Sierpinski antenna and the improves of Koch antenna is described in this paper. Due to its similarity triangular shape and straight line, is compared to well-know single band bow-tie and monopole respectively. Both experimental and numerical results shows that the selfsimilarity properties of the fractal shapes are translated into its electromagnetic behavior. Moreover the space filling properties of many forms can be used to design small antennas as well. The curves obtains are show how fractal monopole can improve the radiation features of a common linear monopole (resonance frequency, radiation resistance, bandwidth).